Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1115/1.1929787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Buoyancy on Heat Transfer in Supercritical Water Flow in a Horizontal Round Tube

Abstract: Heat transfer to supercritical water and buoyancy∕natural convection effects are becoming increasingly important areas of research due to current trends in nuclear reactor design and supercritical water oxidation facilities. A pilot-scale supercritical water oxidation loop was constructed at the University of British Columbia. For this work, the facility was used to study the relative importance of buoyancy effects on supercritical water flowing in a horizontal pipe. Local heat transfer coefficients at the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“…In [9] it studied the horizontal tubes compared with the experiments in [6] and found the Speziale non-linear high Reynolds k-ε turbulence model with the Hassid and Poreh near-wall treatment under y + < 1.0 can give good predictions of the heat transfer of SCW using STAR-CD code. In this paper, the mesh partition method (stretched mesh near wall and general structure mesh inside main flow domain), y + value and the Speziale non-linear high…”
Section: Turbulence Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…In [9] it studied the horizontal tubes compared with the experiments in [6] and found the Speziale non-linear high Reynolds k-ε turbulence model with the Hassid and Poreh near-wall treatment under y + < 1.0 can give good predictions of the heat transfer of SCW using STAR-CD code. In this paper, the mesh partition method (stretched mesh near wall and general structure mesh inside main flow domain), y + value and the Speziale non-linear high…”
Section: Turbulence Modellingmentioning
confidence: 99%
“…2 shows the schematic geometry. The computational test parameters are used same as the experiments in [6]. In the geometry sketch, L is the tube length and D is the tube diameter.…”
Section: Physical Problem and Computational Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this evolution, buoyancy played an important role in heat transfer at supercritical pressures. A number of research papers [35][36][37][38] discussed the effect of buoyancy on heat transfer in supercritical fluids.…”
Section: Introductionmentioning
confidence: 99%
“…evolution, buoyancy played an important role in heat transfer at supercritical pressures. A number of research papers [35][36][37][38] discussed the effect of buoyancy on heat transfer in supercritical fluids. From the above literature review, it can be observed that mixed convection heat transfer in supercritical CO2, flowing vertically in a uniformly-heated circular tube at low mass flux, has not received much research attention.…”
Section: Introductionmentioning
confidence: 99%